2021
DOI: 10.3389/fnsys.2021.746859
|View full text |Cite
|
Sign up to set email alerts
|

Sensory-Evoked 40-Hz Gamma Oscillation Improves Sleep and Daily Living Activities in Alzheimer’s Disease Patients

Abstract: Pathological proteins contributing to Alzheimer’s disease (AD) are known to disrupt normal neuronal functions in the brain, leading to unbalanced neuronal excitatory-inhibitory tone, distorted neuronal synchrony, and network oscillations. However, it has been proposed that abnormalities in neuronal activity directly contribute to the pathogenesis of the disease, and in fact it has been demonstrated that induction of synchronized 40 Hz gamma oscillation of neuronal networks by sensory stimulation reverses AD-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 40 publications
5
38
0
Order By: Relevance
“…Disturbances in daily activity rhythms accelerate the progression from MCI to AD, and a diagnosis of MCI or AD is associated with accelerated worsening of the disturbances [ 50 ]. Our findings of significantly increased day-to-day regularity of activity patterns (IS) over four months in the active group but not the control group are consistent with findings that GENUS light and sound can intervene to improve daily rhythms that ordinarily degrade with age and in AD [ 31 , 73 ]. Sleep may also be affected by combined GENUS stimulation.…”
Section: Discussionsupporting
confidence: 88%
“…Disturbances in daily activity rhythms accelerate the progression from MCI to AD, and a diagnosis of MCI or AD is associated with accelerated worsening of the disturbances [ 50 ]. Our findings of significantly increased day-to-day regularity of activity patterns (IS) over four months in the active group but not the control group are consistent with findings that GENUS light and sound can intervene to improve daily rhythms that ordinarily degrade with age and in AD [ 31 , 73 ]. Sleep may also be affected by combined GENUS stimulation.…”
Section: Discussionsupporting
confidence: 88%
“…This seems to suggest that visual gamma entrainment fundamentally differs from the steady-state responses induced by lower stimulation frequencies, which is in line with theories stating that steady-state responses to higher frequencies have a different cortical distribution compared to those elicited by lower frequencies (Vialatte et al, 2010 ; Wu, 2016 ). A recent paper (Cimenser et al, 2021 ) suggests that the lower frequencies in the gamma range propagate to the larger scalp areas compared to the higher frequencies (including 40 Hz). The authors of this paper however, did not use a task and it is still not clear whether the propagation of the entrainment in combination with a task is different in 40 Hz stimulation from other gamma frequencies.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, methods which increase neural activity during wakefulness, such as TMS, may increase slow-wave activity in subsequent sleep ( Huber et al, 2007 ). In a recent study, 40 Hz visual and auditory stimulation benefitted sleep in a small sample of Alzheimer’s disease patients ( Cimenser et al, 2021 ). Similar stimulation improved pathology in Alzheimer’s disease mouse models ( Addaikkan et al, 2019 ; Iacarino et al, 2016 ; Martorell et al, 2019 ).…”
Section: Translational Approaches To Influence Different Aspects Of S...mentioning
confidence: 99%
“…One possible way that 40 Hz stimulation may improve pathology and cognition is by improving sleep. In a small recent clinical study 14 patients with mild to moderate AD showed improved sleep as assessed by actigraphy measures following 1 h of 40 Hz sensory stimulation/day for 6 months versus 8 sham control subjects ( Cimenser et al, 2021 ). Furthermore, in contrast to the sham stimulation control group which declined in their ability to carry out daily living activities, the stimulation group maintained their ability to function.…”
Section: Non-invasive Stimulation Approachesmentioning
confidence: 99%